Analisis Performa Arsitektur Microservices pada Platform E-Commerce Waltmart Menggunakan Protocol Buffers, Redis Caching, Message Queue, dan Kubernetes - Dennise Adrianto; Herman; William Chang; Richard Delbert Tannady (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Modern e-commerce platforms are required to handle increasing transaction volumes and user traffic while maintaining high performance and scalability. This study evaluates the implementation of a microservices architecture on the Waltmart e-commerce platform to improve performance, scalability, and system reliability. The architecture is designed using independent services supported by Protocol Buffers for efficient inter-service communication, Redis caching for faster data retrieval, and Message Queue (MQ) mechanisms for asynchronous processing. Kubernetes is applied to manage container orchestration and autoscaling under varying traffic loads. Performance evaluation is conducted through load testing by measuring serialization time, response time, and system throughput. The results show that Protocol Buffers reduce serialization and deserialization time by more than 50% compared to JSON, while Redis caching significantly lowers response times and increases throughput. Although the performance improvement from MQ is relatively modest, it enhances system stability during high-volume transactions.